Comparison of mechanical force of manually assisted chiropractic adjusting instruments. - Colloca CJ; Keller TS; Black P; Normand MC; Harrison DE; Harrison DD (Journal of Manipulative & Physiological Therapeutics)
OBJECTIVE: To quantify the force-time and force-delivery characteristics of six commonly used handheld chiropractic adjusting devices. METHODS: Four spring-loaded instruments, the Activator Adjusting Instrument; Activator II Adjusting Instrument, Activator III Adjusting Instrument, and Activator IV Adjusting Instrument, and two electromechanical devices, the Harrison Handheld Adjusting Instrument and Neuromechanical Impulse Adjusting Instrument, were applied to a dynamic load cell. A total of 10 force-time histories were obtained at each of three force excursion settings (minimum to maximum) for each of the six adjusting instruments at preload of approximately 20 N. RESULTS: The minimum-to-maximum force excursion settings for the spring-loaded mechanical adjusting instruments produced similar minimum-to-maximum peak forces that were not appreciably different for most excursion settings. The electromechanical adjusting instruments produced short duration ( approximately 2-4 ms), with more linear minimum-to-maximum peak forces. The force-time profile of the electromechanical devices resulted in a more uniform and greater energy dynamic frequency response in comparison to the spring-loaded mechanical adjusting instruments. CONCLUSIONS: The handheld, electromechanical instruments produced substantially larger peak forces and ranges of forces in comparison to the handheld, spring-loaded mechanical devices. The electromechanical instruments produced greater dynamic frequency area ratios than their mechanical counterparts. Knowledge of the force-time history and force-frequency response characteristics of spinal manipulative instruments may provide basic benchmarks and may assist in understanding mechanical responses in the clinical setting.